La ceca de Ilduro - Sinner, Alejandro G., (Archaeopress Roman archaeology ;, 2017)
This text is exclusively devoted to the mint of Ilduro, its main goal being to study not only the issues produced by the workshop in detail, but also the role that this coinage had in the monetarization of a changing society, that of the Laietani, which had never previously needed to use coinage.